BOGDANOVA E.V. THE STRUCTURE OF THE INCLUSIVE COMPETENCE OF STUDENTS IN THE INFORMATION-EDUCATIONAL ENVIRONMENT OF THE UNIVERSITY - E. V. Bogdanova (Вестник Мининского университета, 2017)
In the article the analysis of scientific pedagogical sources, which explores the structure of professional competence of teachers. The interpretation of this concept is seen by different authors in psychological and pedagogical research, and currently there is no unambiguous definition of professional competence. Because of the inclusive competence of students to apply to the category of professional competence and has its own structure, us in particular, and describes the structure of the inclusive competence of students in the information educational environment of the University. This competence reflects the specifics of the particular sphere of professional activity, i.e. inclusive education. The structure of the inclusive competence of students related to professional competencies and consists of motivation, reflective and cognitive information components. Key content competencies included in the inclusive competence, can be interpreted as the ability of understanding the content of professional activity in the conditions of inclusive education.